Developing the Product Unloading Queue Process to Increase Efficiency in Receiving Products : Case Study Dohome Public Company Limited, Phetkasem Branch - จันทิมา, สุดารัตน์; เปรมเดช, ณาฬิษา; กมลสุนทรโรจน์, สุรินทร์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to develop a product delivery queue booking process to enhance the efficiency of goods receiving, using a case study of DoHome Public Company Limited, Phetkasem Branch. The objective is to streamline the work process, reduce the time spent on queue booking, and improve the accuracy of customer data entry. The target population includes customers who propose products to the company. The study found that the primary issue lies in the inefficiency of telephone communication due to poor signal quality, resulting in prolonged conversations and repeated questions. This leads to errors in recording delivery dates and quantities, and causes delays. Therefore, an idea was proposed to improve the efficiency of the queue booking process through the development of a mobile application. This approach helps increase accuracy, minimize customer data errors, enhance goods receiving efficiency, reduce operational steps, and alleviate the workload of employees.However, the proposed system represents a recommendation for future development based on the current process. It is suggested that additional functionalities be added to the system and that steps for employees be further simplified—either by creating a new application or improving the existing system. Several factors must be considered, such as budget, labor, project duration, company data confidentiality, and executive approval, as DoHome Public Company Limited is a large organization.The development requires input from various departments and involves a complex application database, part of which contains confidential information. Hence, a platform prototype was created to demonstrate simplicity, user-friendliness, data accuracy, and the potential benefits of a fully developed queue booking system to support and facilitate operational efficiency.